KONDISI LINGKUNGAN DI DAERAH YANG PERNAH MENGALAMI KEJADIAN LUAR BIASA JAPANESE ENCEPHALITIS - Nurhidayah, Nurhidayah; Sutarga, Made; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2019)
ABSTRACT Canggu Village is an area that has experienced outbreaks of Japanese encephalitis (JE) in 2015 by JE clinical cases as many as 18 cases. This study aims to determine the environmental conditions, of JE prevention in the village of Canggu. This research is a descriptive cross-sectional design. The sampling technique using quota sampling, from 7 hamlets in the village of Canggu taken each 22 respondents to be sampled in the study to meet the minimum required quota sample. The sampling of this research are respondent that live in radius 100 meters from pig stable. The number of respondents in the interview are as many as 151 people consisting of 17 patients and 134 non JE. The results showed that 82.84% of respondents have a risky environment, whereas respondents that stay near rice terraces 14,28% get JE and respondent that around their house there is a dirty puddle 28,57% get JE. The conclusion from this study is most respondents have a risk of environmental conditions. Where the most part of them is stay close to the field. It is recommended that the government to provide education or counseling equitably to community, not only who have experienced clinical symptoms of JE but also high-risk society. Keywords: Japanese encephalitis, Environmental Conditions, Outbreak